2005
DOI: 10.1136/bmj.38327.648472.82
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke and risk of respiratory cancer and chronic obstructive pulmonary disease in former smokers and never smokers in the EPIC prospective study

Abstract: Objectives To investigate the association between environmental tobacco smoke, plasma cotinine concentration, and respiratory cancer or death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
166
2
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(191 citation statements)
references
References 10 publications
12
166
2
9
Order By: Relevance
“…ETS has been shown to be a likely risk factor for coronary artery disease, 1 2 stroke, 3 lung cancer, 4 5 and obstructive lung disease. [5][6][7] Respiratory symptoms are associated with both personal smoking 8 9 and ETS. 10 11 Most studies on the effect of ETS on respiratory health show a higher effect of ETS at the workplace compared with ETS at home, 10 12 13 usually interpreted as a dose response effect as the level of ETS is higher at work than at home for most subjects.…”
mentioning
confidence: 99%
“…ETS has been shown to be a likely risk factor for coronary artery disease, 1 2 stroke, 3 lung cancer, 4 5 and obstructive lung disease. [5][6][7] Respiratory symptoms are associated with both personal smoking 8 9 and ETS. 10 11 Most studies on the effect of ETS on respiratory health show a higher effect of ETS at the workplace compared with ETS at home, 10 12 13 usually interpreted as a dose response effect as the level of ETS is higher at work than at home for most subjects.…”
mentioning
confidence: 99%
“…Results from a meta-analysis [51] and a comprehensive review [52] showed a relative risk between 1.14 to 5.20 in people who had never smoked but who lived with a smoker. A more recent study reported that passive smoking during childhood increased lung cancer risk in adulthood by 3.6 fold [53]. However, Kofahi and Haddad [37] reported that 58% of university students did not agree that secondhand smoke is a cancer risk.…”
Section: Discussionmentioning
confidence: 96%
“…La presencia de síntomas respiratorios también se encontró asociada a otros factores descritos en la literatura científica, como factores de riesgo para la presencia de enfermedad respiratoria en la población adulta mayor, como son la edad, el sexo (29,30), el consumo de cigarrillo (31,32), la humedad en la vivienda (33)(34)(35)(36), la condición socioeconómica (37)(38)(39)(40), la afiliación a la seguridad social, la presencia de enfermedades concomitantes y otras fuentes de contaminación atmosférica como la ocupacional (41,42) y la cercanía a cultivos de caña de azúcar, que son quemados para su cosecha (43).…”
Section: Discussionunclassified